Seawater desalination using air gap membrane distillation – An experimental study on membrane scaling and cleaning - Hung, Duong Cong; Son, Luong Trung; Thao, Pham Manh; Nguyen, Huynh Thai (Vietnam Journal of Science and Technology, 2017)
The connection between operating temperature and membrane scaling/cleaning during an air gap membrane distillation (AGMD) process of seawater has been systematically elucidated in this study. Experimental and mathematically simulated data demonstrate the profound influences of feed salinity and membrane scaling on water flux at various operating temperatures. Feed salinity exerted significant impacts on water flux at high operating temperatures because of aggravated polarization effects. Membrane scaling and the subsequent membrane cleaning efficiency were also strongly affected by operating temperatures. Indeed, membrane scaling was more severe and occurred at a lower water recovery when operating at 60-50 °C (feed-coolant temperature) compared to that at 35-25 °C. Moreover, membrane cleaning with fresh water and vinegar was less effective for the membrane scaled at 60-50 °C compared to 35-25 °C. Finally, membrane cleaning using vinegar was much more efficient than fresh water. Given the availability of vinegar at household level, vinegar cleaning can potentially be a low cost and readily accessible approach for MD maintenance for small scale seawater desalination applications in remote coastal communities.